QUALIDADE MICROBIOLÓGICA DE MÉIS ARTESANAIS COMERCIALIZADOS NA 11ª FEIRA DO MEL DE SANTA ROSA – RS - SCHIAVO, ANDERSON G.; BALBOM, CATIANI B.; BALBOM, ÉVERTON B.; OLIVEIRA, MARLON L. D.; DINON, PATRICIA; FIORENTINI, ÂNGELA M. (Salão do Conhecimento, 2013)
Resumo